The transcription factor VvWRKY33 is involved in the regulation of grapevine (Vitis vinifera) defense against the oomycete pathogen Plasmopara viticola. Issue 3 (9th October 2014) - Merz, Patrick R.; Moser, Tina; Höll, Janine; Kortekamp, Andreas; Buchholz, Günther; Zyprian, Eva; Bogs, Jochen
<x xml:space="preserve">Abstract</x> Grapevine (Vitis vinifera ssp. vinifera) is one of the most important fruit species; however, it is highly susceptible to various pathogens, which can cause severe crop losses in viticulture. It has been shown that several WRKY class transcription factors (TFs) are part of the signal transduction cascade, which leads to the activation of plant defense reactions against various pathogens. In the present investigation, a full‐length cDNA was isolated from V. vinifera leaf tissue encoding a predicted protein, designated VvWRKY33, which shows the characteristics of group I WRKY protein family. VvWRKY33 induction correlates with the expression of VvPR10.1 (pathogenesis‐related 10.1) gene in the leaves of the resistant cultivar 'Regent' after infection with Plasmopara viticola, whereas in the susceptible cultivar 'Lemberger' VvWRKY33 and VvPR10.1 are not induced. Corresponding expression of the TF and VvPR10.1 was even obtained in uninfected ripening berries. In planta, analysis of VvWRKY33 has been performed by ectopic expression of VvWRKY33 in grapevine leaves of greenhouse plants mediated via Agrobacterium tumefaciens transformation. In consequence, VvWRKY33 strongly increases resistance to P. viticola in the susceptible cultivar 'Shiraz' and reduces pathogen sporulation of about 50–70%, indicating a functional role for resistance in grapevine. Complementation of the resistance‐deficient Arabidopsis thaliana Columbia‐0 (Col‐0) mutant line wrky33‐1 by constitutive expression of VvWRKY33 restores resistance against Botrytis cinerea to wild‐type level and in some complemented mutant lines even exceeds the resistance level of the parental line Col‐0. Our results support the involvement of VvWRKY33 in the defense reaction of grapevine against different pathogens.